Evaluation of Leishmanization Using Iranian Lizard Leishmania Mixed With CpG-ODN as a Candidate Vaccine Against Experimental Murine Leishmaniasis - Keshavarzian, Nafiseh; Noroozbeygi, Mina; Haji Molla Hoseini, Mostafa; Yeganeh, Farshid (Frontiers in Immunology, 2020)
Background and Objectives: The live non-pathogenic Leishmania tarantolae has recently provided a promising approach as an effective vaccine candidate against experimental leishmaniasis (ILL). Here, we evaluated the immunoprotective potential of the live Iranian Lizard Leishmania mixed with CpG adjuvant against L. major infection in BALB/c mice. Methods: Four groups of female BALB/c mice were included in the study. The first and second groups received PBS and CpG, respectively. The immunized groups received 2 × 105 ILL promastigotes and the CpG-mixed ILL (ILL+CpG). Injections were performed subcutaneously in the right footpad. Three weeks later, all mice were challenged with 2 × 105 metacyclic promastigotes of Leishmania majorEGFP; inoculation was done in the left footpad. The measurement of footpad swelling and in vivo fluorescent imaging were used to evaluate disease progress during infection course. Eight weeks after challenge, all mice were sacrificed and the cytokines levels (IFN-γ, IL-4, and IL-10) and sera antibodies concentrations (IgG2a and IgG1) using ELISA assay, nitric oxide production using Griess assay, and arginase activity in cultured splenocytes, were measured. In addition, direct fluorescent microscopy analysis and qPCR assay were used to quantify the splenic parasite burden. Result: The results showed that mice immunized with ILL+CpG were protected against the development of the dermal lesion. Moreover, they showed a significant reduction in the parasite load, in comparison to the control groups. The observed protection was associated with higher production of IFN-γ, as well as a reduction in IL-4 level. Additionally, the results demonstrated that arginase activity was decreased in ILL+CpG group compared to other groups. Conclusion: Immunization using ILL+CpG induces a protective immunity; indicating that ILL with an appropriate adjuvant would be a suitable choice for vaccination against leishmaniasis.